Granulomatose de Wegener: aspectos na tomografia computadorizada de tórax - Monteiro, Evelise de Azevedo (2004)
Wegener granulomatosis (WG) is an idiopathic systemic vasculitis with necrosis that results from an inflammation involving mainly small vessels. The disease may present one of two forms: the limited and the classic ones. In this paper the CTs of twelve patients with WG who developed pulmonary disease were retrospectively analized. They were selected through analisis of thier medical records and came from four different states of our country, therefore it was not possible to standardize their routine tomographic examinations. Their computed tomography chest scans were then analyzed to show the more common findings and its pattern of distribution. The most common findings were masses and nodules (58,3%), consolidations (50%), ground glass areas (41,6%), cavitations (41,6%), halo sign (25%), peribronchovascular consolidations(16,6%), pleuritis (16,6%), thickening of interlobular septa (8,3%), and bronchium walls (8,3%). On the whole, the radiological abnormalities of GW are generally varied and unespecific. Nevertheless the computed tomography chest scans and, most of all, the high resolution computed tomography chest scans are the best means to estimate the lung involvement that occurs in GW, and are also very useful to evaluate the activity of the disease when associated with clinical data and broncoscopy.